Lateral Temporal Subcutaneous Brow Lift: Clinical Experience and Systematic Review of the Literature. Issue 4 (24th April 2020) - Savetsky, Ira L.; Matarasso, Alan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Numerous techniques have been described to correct brow aesthetics in facial rejuvenation. We report the senior author's (A.M.) current approach for eyebrow elevation utilizing a lateral subcutaneous brow lift and, when indicated, a medial subgaleal brow lift. Furthermore, a systematic review of the literature was performed comparing the different surgical approaches and techniques. Methods: A systematic review of the literature was performed using the MEDLINE, PubMed, and Cochrane Central Register of Controlled Trials databases. Studies were included if the content was original, provided outcome data, and complications. Results: The senior author (A.M.) has performed over 500 lateral temporal subcutaneous brow lifts for lateral brow ptosis. The vast majority was highly satisfied with the outcome and there were minimal complications. This represents the largest series of patients utilizing this technique. Twenty-six articles were reviewed and 5 met our screening criteria and were analyzed critically for inclusion and further objective review. All of the studies were retrospective in nature and report high patient satisfaction with an acceptable risk profile. Conclusions: In this study, we described the largest series of patients undergoing lateral subcutaneous brow lifts (n > 500), as well as a systematic review of the current literature. The current literature described an overall high degree of patient satisfaction with low complication rates, similar to the senior author's (A.M.) experience. This technique has emerged as a reliable technique for lateral brow elevation with a very low and acceptable risk profile.